2017
DOI: 10.1002/jqs.2951
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the Quaternary evolution of the Bristol Channel, UK

Abstract: A synthesis of new publically available borehole and bathymetric data, combined with a wealth of other existing disparate data sources, reveals new insights into the Quaternary history of the Bristol Channel area. Sediment boreholes throughout the Bristol Channel confirm the area was glaciated in the Pleistocene. Till is present below marine deposits and, in some areas, is visible morphologically as submerged moraines. In the central and eastern Bristol Channel the submerged valley course of the palaeo‐Severn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…Third, recent bathymetric data (Gibbard et al . ) reveal the probable LGM end moraine to an ice lobe filling Swansea Bay, supporting previous sea‐floor sediment investigations (Blackley ; Culver & Bull ), recent views about LGM ice encroachment onto southeast Gower (Hiemstra et al . ) and icecap modelling (Patton et al .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Third, recent bathymetric data (Gibbard et al . ) reveal the probable LGM end moraine to an ice lobe filling Swansea Bay, supporting previous sea‐floor sediment investigations (Blackley ; Culver & Bull ), recent views about LGM ice encroachment onto southeast Gower (Hiemstra et al . ) and icecap modelling (Patton et al .…”
Section: Discussionsupporting
confidence: 85%
“…Confinement of the southern limit of the ice lobe to the peninsula is supported by: (i) glacigenic sediment in dry valley fans between Eastern Slade and Oxwich Point being relatively small in calibre, sparse and mostly mixed with limestone head, contrasting with fans immediately adjacent to the moraine where it occurs as thick discrete lenses that include some coarse clasts and a mixed glacigenic–limestone diamict; and (ii) recent bathymetric data showing no evidence of moraine development offshore from west Gower (Gibbard et al . ). We attribute the subdued morphology of the W–E section of the moraine in large part to the influence of an extensive network of sinks and passages in the underlying limestone (J. Cooper, pers.…”
Section: Discussionmentioning
confidence: 97%
“…1; cf. Rolfe et al ., 2012) although the nature of any direct evidence of glaciation and associated timings in the outer Bristol Channel remain equivocal (Carr et al ., 2017; Gibbard et al ., 2017; Hiemstra et al ., 2019). However, the distribution of glacigenic sediments and landforms on Scilly (Scourse, 1991; Hiemstra et al ., 2006; Smedley et al ., 2017a) is difficult to explain without a major portion of the ISIS east flank overriding at least the western part of the Lundy Platform (Lockhart, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gibbard et al . (2017) showed outer end moraine underlying westerly Nash Sands, which correspond with the undulating morphology marked ‘glacial till’ in Fig. 2.…”
Section: Background To Nash Sands and Its Environmentmentioning
confidence: 61%
“…During the Flandrian transgression (3 to 5 ka BP), sea level reached its present level in the Bristol Channel (Jennings et al, 1998) and the modern tidal regime became established (Stride & Belderson, 1990). Gibbard et al (2017) showed outer end moraine underlying westerly Nash Sands, which correspond with the undulating morphology marked 'glacial till' in Fig. 2.…”
Section: Background To Nash Sands and Its Environmentmentioning
confidence: 90%